2017
DOI: 10.4046/trd.2017.80.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Lung Regeneration Therapy for Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a critical condition with high morbidity and mortality. Although several medications are available, there are no definite treatments. However, recent advances in the understanding of stem and progenitor cells in the lung, and molecular changes during re-alveolization after pneumonectomy, have made it possible to envisage the regeneration of damaged lungs. With this background, numerous studies of stem cells and various stimulatory molecules have been undertaken, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Recent studies have begun targeting RARs in an isoform-specific manner using isoform-specific pharmacological agonists and inhibitors for improved selectivity and function. Regenerative studies in skeletal muscle in the mouse have recently demonstrated that selective receptor isoform agonism of RARg improved muscle regeneration 46 , as well as moving to RARg isoform-selective Phase I and Phase II trials in lung regeneration 47 , clinical trials achieving positive results yet limited by small patient cohort 48 . Targeting of specific RAR isoforms has not yet been tested as a strategy for salivary gland regeneration; however, our results indicate that the behavior of K5 C cells is under complex control by RARs during development.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have begun targeting RARs in an isoform-specific manner using isoform-specific pharmacological agonists and inhibitors for improved selectivity and function. Regenerative studies in skeletal muscle in the mouse have recently demonstrated that selective receptor isoform agonism of RARg improved muscle regeneration 46 , as well as moving to RARg isoform-selective Phase I and Phase II trials in lung regeneration 47 , clinical trials achieving positive results yet limited by small patient cohort 48 . Targeting of specific RAR isoforms has not yet been tested as a strategy for salivary gland regeneration; however, our results indicate that the behavior of K5 C cells is under complex control by RARs during development.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy is applied in regenerative medicine since it is capable of inducing neoangiogenesis, osteogenesis, and remodeling through stem cell stimulation [ 20 ]. On the other hand, while regenerative therapy applied to mice with induced emphysema has shown promising results [ 6 ], clinical trials performed in COPD patients were discouraging [ 6 , 7 ]. Since the human lung also in adulthood maintains a significant regenerative potential [ 17 19 ], due to proliferation of differentiated of stem/progenitor cells and/or by their stimulation [ 18 , 19 ], we here investigated the proliferative action of ESW at low dosage in bronchial epithelial cells and in primary bronchial fibroblasts of control smokers (CS) and patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Regenerative therapy for COPD includes mesenchymal stromal cell (MSC) or tissue engineering therapies. But, while bone marrow MSC or adipose tissue MSC treatments showed promising results in mice with induced emphysema [ 6 ], clinical trials performed in COPD patients have been discouraging [ 6 , 7 ]. There are a large number of animal studies in which lung regeneration has been successfully stimulated.…”
Section: Introductionmentioning
confidence: 99%
“…On their review, Oh et al [50] show positive perspectives on lung regeneration therapy, but they point out that the use of this therapy remains unclear and must be tested in better-designed clinical trials. The authors call attention to stem cells' tumorigenicity properties and the use of retinoids, because they can lead to cancer or vascular diseases.…”
Section: Interventions For Emphysema: Effectiveness and Safetymentioning
confidence: 99%